P-282 Rennie grove hospice care preceptorship programme. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Clarke, Jo
Abstract : Background: The hospice has developed a preceptorship programme in response to the national shortage of nurses and the increasing demand for its service with increase in referrals year on year. We have begun to see the effects of the national shortage in nurses in our own recruitment. After 30 years of caring for our patients and having asked for experience in palliative care or community experience we decided to make the move away and recruit newly qualified nurses after a robust recruitment process. Aims: to develop a preceptorship programme for newly qualified staff to run over 12 months write a job description and role profile write interview questions, marking grid and scenarios for interview write a competency framework prepare the existing workforce of 90-strong nurses to support and co-mentor the preceptees write preceptee guidelines and prepare the preceptors for their new roles run an initial pilot with two preceptees. Method: Completed a literature search around preceptorship programmes in the community and hospice arenas; explored what was happening in other areas; looked at the NMC code and aligned competencies with the code; aligned competencies with e-lfh; used the RCN framework for nurses working in specialist palliative care; attended job fairs at the local universities to advertise the programme. Results: The interviewing process and questions was effective in selecting two candidates; the preceptorship programme and frame work has yet to be tested; a full-12 month programme is ready for successful candidates to undertake. Conclusion: We are still looking to recruit suitable candidates for the programme and have identified that we would be in a stronger position if we were to take third year students and those doing the return to practice course. To this end we have approached two universities to support existing mentors to become 'sign off' mentors.